Severe malaria in children leads to a significant impairment of transitory otoacoustic emissions - a prospective multicenter cohort study. Issue 1 (December 2015) - Schmutzhard, Joachim; Lackner, Peter; Helbok, Raimund; Hurth, Helene; Aregger, Fabian; Muigg, Veronika; Kegele, Josua; Bunk, Sebastian; Oberhammer, Lukas; Fischer, Natalie; Pinggera, Leyla; Otieno, Allan; et al.
Abstract Background Severe malaria may influence inner ear function, although this possibility has not been examined prospectively. In a retrospective analysis, hearing impairment was found in 9 of 23 patients with cerebral malaria. An objective method to quickly evaluate the function of the inner ear are the otoacoustic emissions. Negative transient otoacoustic emissions are associated with a threshold shift of 20 dB and above. Methods This prospective multicenter study analyses otoacoustic emissions in patients with severe malaria up to the age of 10 years. In three study sites (Ghana, Gabon, Kenya) 144 patients with severe malaria and 108 control children were included. All malaria patients were treated with parental artesunate. Results In the control group, 92.6 % (n = 108, 95 % confidence interval 86.19–6.2 %) passed otoacoustic emission screening. In malaria patients, 58.5 % (n = 94, malaria vs controlsp < 0.001, 95 % confidence interval 48.4–67.9 %) passed otoacoustic emission screening at the baseline measurement. The value increased to 65.2 % (n = 66, p < 0.001, 95 % confidence interval 53.1–75.5 %) at follow up 14–28 days after diagnosis of malaria. The study population was divided into severe non-cerebral malaria and severe malaria with neurological symptoms (cerebral malaria). Whereas otoacoustic emissions in severe malaria improved to a passing percentage of 72.9 % (n = 48, 95 % confidence interval 59–83.4 %) at follow-up, the patients with cerebral malaria showed a drop in the passing percentage to 33 % (n = 18) 3–7 days after diagnosis. This shows a significant impairment in the cerebral malaria group (p = 0.012 at days 3–7, 95 % confidence interval 16.3–56.3 %;p = 0.031 at day 14–28, 95 % confidence interval 24.5–66.3 %). Conclusion The presented data show that 40 % of children have involvement of the inner ear early in severe malaria. In children, audiological screening after severe malaria infection is not currently recommended, but is worth investigating in larger studies.